PENERAPAN GOOD CORPORATE GOVERNANCE YANG DILAKSANAKAN OLEH PT. PERIKANAN INDONESIA (PERSERO): Implementation Of Good Corporate Governance By Limited Liability Company Perikanan Indonesia (Persero) - Piere Marquez Vandante; Siti Nurbaiti (Reformasi Hukum Trisakti, 2025)
The Indonesian government, through the Ministerial Regulation of State-Owned Enterprises No. Per-2/MBU/03/2023, mandates the implementation of Good Corporate Governance (GCG) in state-owned companies to support national economic growth. However, its implementation at PT. Perikanan Indonesia (Persero) in 2022 raised several issues. With the formulation of the problem is how the implementation of Good Corporate Governance (GCG) is carried out by PT Perikanan Indonesia (Persero). This study utilizes a normative and descriptive method, using secondary data that is analyzed qualitatively with conclusions drawn deductively. The research findings and the result, indicate that PT. Perikanan Indonesia (Persero) has not shown strong commitment to the principles of GCG. Despite having Corporate Governance Guidelines and a Code of Conduct, PT. Perikanan Indonesia (Persero) has violated several GCG principles, including transparency, accountability, and responsibility. The application of GCG in this company needs improvement to meet established standards and to enhance corporate performance and integrity.